Perancangan Sistem Informasi Akuntansi Persediaan Bahan Baku Pada PT Warung Pasta Dengan Menggunakan Software Microsoft Visual Basic 6.0 dan SQL Server 2000 Berbasis Client Server - Apriani Puti Purfini; Nuri Nurjannah; Dony Waluya Firdaus (Labkat Press KA FTIK UNIKOM, 2012)
PT Warung Pasta located at Ganesha No. 04 Bandung, Phone. 022-2500416 is a manufacturing company moving on the culinary area. At the time of implementing the accounting records and updating the inventory of raw material to the company's use Microsoft Office Excel software. These problems result in ineffective and optimal performance of all divions of the company contained in the provider of information and reports required. From the matter above, the writer take the title